World Stage, local dramas? The World Heritage designations of Shark Bay and Ningaloo Reef - Hughes, Michael; Jones, Roy; Jones, Tod; Christensen, J. (Macquarie University, 2012)
World Heritage status can both confer prestige on and potentially attract tourists to the areas so designated. However such designations can also lead to increased restrictions being imposed on an area’s local residents. In remote areas such as Western Australia’s Gascoyne region, where the challenges of both distance and low population numbers are extreme and government restrictions on the inhabitants were concomitantly light, local adaptation to World Heritage designation can be particularly challenging. The World Heritage designation of Shark Bay in 1991 was the first in Western Australia and occurred in the context of promises made during a federal election campaign. Both here and, much more recently, at Ningaloo, sections of the local populations therefore saw the World Heritage initiatives as being driven by ‘outsiders’ and reacted to the designation processes with suspicion and concern, fearing both loss of access to land and restrictions on a range of outdoor activities. Some Shark Bay residents travelled to Ningaloo (and a Ningaloo resident travelled to UNESCO in Paris) to campaign against the area’s 2011 designation, linking the two areas through spreading a fear of loss of local control. Increasing regulation from state agencies in both locations during the years before the World Heritage listing processes influenced local responses. This paper will report on the preliminary findings from a survey of both the literature and a range of local stakeholders of the community impacts of World Heritage designation on both localities.